Danny Phantom : the complete series. [videorecording (DVD)] - Hartman, Butch
Ready to take a trip to the other side? Well, chill with all of the frighteningly good episodes from the complete series of Danny Phantom! Find out how an average kid became part ghost, and all ghost hunter! Then join Danny and pals Sam and Tucker on otherworldly adventures up close and personal with Technus, the Spectral Master of all things technological; Penelope Spectra, a ghost who feeds off teen misery; and Danny's archenemy, Vlad Plasmius.